2021
DOI: 10.3390/v13071210
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic Trafficking Perturbation Induced by Picornaviruses

Abstract: Picornaviruses are positive-stranded RNA viruses. Even though replication and translation of their genome take place in the cytoplasm, these viruses evolved different strategies to disturb nucleocytoplasmic trafficking of host proteins and RNA. The major targets of picornavirus are the phenylalanine-glycine (FG)-nucleoporins, which form a mesh in the central channel of the nuclear pore complex through which protein cargos and karyopherins are actively transported in both directions. Interestingly, while entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 81 publications
1
24
0
Order By: Relevance
“…Picornaviruses cause a so-called nucleocytoplasmic traffic disorder by modulating the nuclear pore complexes and thereby disrupting the regulated transport of material, i.e., proteins and mRNA, in and out of the nucleus ( Lidsky et al., 2006 ; Lizcano-Perret and Michiels, 2021 ). Interestingly, we also observed a relocalization of GFP-HSBP1 from the cytoplasm into the nucleus upon EMCV infection by fluorescence microscopy ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Picornaviruses cause a so-called nucleocytoplasmic traffic disorder by modulating the nuclear pore complexes and thereby disrupting the regulated transport of material, i.e., proteins and mRNA, in and out of the nucleus ( Lidsky et al., 2006 ; Lizcano-Perret and Michiels, 2021 ). Interestingly, we also observed a relocalization of GFP-HSBP1 from the cytoplasm into the nucleus upon EMCV infection by fluorescence microscopy ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that GFP-HSBP1 translocation into the nucleus depends on L since infection with EMCV-Zn, an EMCV strain lacking L ( Hato et al., 2007 ), did not lead to the same change ( Figures S3C, D ). The mechanism underlying nucleocytoplasmic traffic disorders differs between members of the cardioviruses ( Picornaviridae ) like EMCV and members of the enteroviruses ( Picornaviridae ) such as CVB3 and EV71 ( Lizcano-Perret and Michiels, 2021 ). Thus, we tested whether the relocalization of HSBP1 is specific to EMCV or also occurs upon infection with CVB3 and EV71.…”
Section: Resultsmentioning
confidence: 99%
“…However, several viruses, including picornaviruses, subvert the host nucleocytoplasmic trafficking machinery to their benefit during infection (Figure 2) [334,[351][352][353]. Different viruses, many of which rely on IRES-dependent translation initiation for the synthesis of their proteins, use different mechanisms to co-opt the cell's nucleocytoplasmic trafficking machinery (for reviews, see [334,[351][352][353]). For enteroviruses and rhinoviruses, 2A and 3C proteases are important for the process [191,[354][355][356][357].…”
Section: Most Itafs Are Nucleus-cytoplasmic Shuttling Rna-binding Proteinsmentioning
confidence: 99%
“…In aphthoviruses, the 3C protease is used [358], while cardioviruses need their L protein [359]. Nucleocytoplasmic protein relocalization during viral infection is not just a spillover event associated with viral infection as control nuclear proteins remain in the nucleus [351][352][353]360]. Proteins from the hnRNP family may, for example, associate with other proteins linked with pre-mRNA metabolism, such as members of the serine/arginine (SR)-rich protein family of splicing factors [336], relocalize as a complex and stimulate viral IRES-mediated translation in the cytoplasm.…”
Section: Most Itafs Are Nucleus-cytoplasmic Shuttling Rna-binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation